An Ordinance Relating to Offenses and Disorderly Conduct and Repealing Ordinances no. 152, 178, & 471, Olympia City Council, Ordinance no. 523, §§ 4-5 (Washington, 1891). - (:unkn) unknown (My University, 1891)
That any person who shall within the following limits, to-wit: Beginning at the intersection of Fifteenth and Eastside streets; thence north on line of said Eastside street to a point known as the Priest Place; thence west to a point five hundred yards west of the west shore of Budd's Inlet; thence south to the line of said Fifteenth street, and thence east to place of beginning, fire off or discharge any gun, pistol or fire arm of any kind, shall upon conviction thereof before a police justice of said city be fined in any sum not less than five nor more than twenty five dollars, and in default of the payment thereof, shall be committed to the city jail until such fine and costs are paid, not to exceed ten days.
Keywords: DISCHARGE